Smart cities as a form of governance for sustainability. A comparative case study in Germany, France and Luxembourg. - Körber, Teresa (Nomos, 2019)
Population in cities is increasing and the emerging problems need to be tackled. In this context, the Sustainable Development Goals (SDGs) are of high importance and the smart city concept with a governance model involving city’s stakeholders is arising. The aim of smart cities is to improve the citizens’ quality of life. In this regard, it is necessary to find out which SDGs the cities are working on, especially the targets of SDG 11. Furthermore, research is needed on the role of stakeholders in smart cities. To analyse this topic, a narrative review of literature and comparative multiple case study methodology is chosen. The analysis shows that cities are working on SDGs, but in the context of smart city the SDGs are not as present as expected. All three cities from the case studies are at the beginning of transformation. In addition, diverse stakeholders are involved in a smart city. In the future, smart cities must communicate their contribution to the SDGs and continue to incorporate all urban actors to work on them. For further research a more comprehensive analysis is required qualitatively or quantitatively.
Keywords: Smart City; Nachhaltige Stadtentwicklung; Planungsziel; Interkommunale Zusammenarbeit; Stakeholder; Sustainable Development Goals